Formulasi dan Evaluasi Sabun Cair Ekstrak Etanol Okra (Abelmochus esculentus) serta Uji Antibakterinya: Formulation and Evaluation of Okra (Abelmochus esculentus) Ethanol Extract Liquid Soap and Its Antibacterial Test - Martina, Shofie Fitria; Rohmah, Jamilatur (Universitas Muhammadiyah Sidoarjo, 2019)
Liquid soap is a liquid form that serves to cleanse the skin. The aim of this research are to know the optimization formulation and evaluation of liquid soap extract ethanol okra ( ) and also find the best concentration of okra extract as the inhibitors against Staphylococcus . Experimental laboratory was chosen as the research design. Liquid soap consists of 5 formulations, namely formulation 1, 2, 3, 4, and 5 which consist of 0%, 25%, 50%, 75% and 100% okra concentration. The antibacterial effectiveness was tested by disc method against liquid soap extract ethanol okra ( ) and the clear zone measured. The analysis done with two-way test. The results of the evaluation of liquid soap quality was appropriate with the standard of soap quality established by SNI 1994. The best moisture value found in the formulation of 5 (F5) with 0%form of 3.54%, the best free fatty acid found in formulation 4 (F4) with a concentration of 50% of 0.07135%, the best free alkali concentration was found in formulation 2 (F2) with a 25% concentration of 0.04194%, the best pH value was presented at concentrations of 0%, 25%, and 50% with a value of 9, the best value of foam stability found in Formula 1 (F1) with a 100% concentration of 9.1, the best density (BJ) test found in Formula 4 (F4) with 0% concentration. The result of ANOVA test with variation of ethanol okra concentration obtained p-value = 0.000 <0.05 which states there was a significant difference where liquid soap extract ethanol okra has antibacterial to Staphylococcus . The best inhibitory zone test resulted in formation 5 (F5) of 14.7 mm at 100% concentration.